Sessiz Ev'in Çok Sesliliğinde Groteskin Sesini Duymak - Burcu Uşaklı Sandal (Akademik Dil ve Edebiyat Dergisi, 2026)
ABSTRACT Having placed postmodern techniques at the basis of his works, Orhan Pamuk frequently benefited from these techniques in his second novel, Silent House, published in 1983. In this sense, the concept of polyphony, in which the narration is made through various sources rather than a single source, stands out in the novel. Polyphony enables the text to have a multi-layered quality; the narrator constantly changes within the text, thus the novel takes on a varied structure, as in Mikhail Bahtin’s concept of carnival. Moreover, this carnivalesque structure is supported by the descriptions of the summer house, which forms the main place of the text, and the events experienced by the three generations who came together in this house. On the other hand, in order to diversify the carnival, Pamuk also included the grotesque body, which is an integral part of it. The grotesque body, pushed out of society and condemned to live with the misfortune of its deformity, stands right next to the sublime, turning the text inquestion into a carnival venue. Based on this, this study will examine the position of the grotesque body in Silent House and its function within the text.